2011
DOI: 10.1007/s00540-011-1176-6
|View full text |Cite
|
Sign up to set email alerts
|

Propofol increases the rate of albumin-unbound free midazolam in serum albumin solution

Abstract: Propofol and midazolam have a synergistic anesthetic action. One of the reasons for this is thought to be the inhibitory effect of propofol on midazolam metabolism. However, because both drugs bind strongly to serum protein, their interaction may not only involve the effects of propofol on midazolam metabolism, but may also involve propofol's effects on serum protein-binding. Against this background, we investigated the characteristics of midazolam binding to serum albumin, and evaluated the effects of both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The absence of propofol peaks at such high concentrations brings up an interesting aspect of propofol biochemistry; namely, that propofol is known to complex with proteins in serum. 4,30,31 The protein–propofol complexation competes with PDMS for the accumulation of propofol, reducing the SPME effect. The quantitative traits of this competitive partitioning warrants further study.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of propofol peaks at such high concentrations brings up an interesting aspect of propofol biochemistry; namely, that propofol is known to complex with proteins in serum. 4,30,31 The protein–propofol complexation competes with PDMS for the accumulation of propofol, reducing the SPME effect. The quantitative traits of this competitive partitioning warrants further study.…”
Section: Resultsmentioning
confidence: 99%
“…The protein binding rates of remimazolam and propofol are 92% [ 18 ] and 98% [ 19 , 20 ], respectively. Propofol causes an increase in midazolam blood concentrations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanistic interpretation is consistent with the results of the present study. Moreover, one study reported that propofol competitively reduced the rate of albumin binding with midazolam (Ohmori et al, 2011 ). Competitive drug interactions between these two drugs may also underlie the results of the present study because propofol and BZD bind strongly to serum proteins.…”
Section: Discussionmentioning
confidence: 99%